PREDICTING BANKRUPTCY IN INDONESIA'S AIRLINE SECTOR: A ZMIJEWSKI MODEL ANALYSIS - Sri Wahyu Handayani; Abednego Priyatama (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to determine the analysis of bankruptcy potential based onThe Zmijewski model was applied to aviation subsector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2022 period. The data used in this study is quantitative, and the data sources are secondary data, with data collection techniques using literature and documentation. The method used in this study is descriptive with a quantitative approach. This method aims to describe a condition in detail by using numbers to process and interpret data. The analysis technique used in this study is the Zmijewski method using 3 ratios. Based on the results of this study, it can be concluded that using the Zmijewski method, all 3 aviation subsector companies have the potential to go bankrupt. The aviation subsector companies listed on the IDX are: PT AirAsia Indonesia Tbk (CMPP), PT Garuda Indonesia (Persero) Tbk (GIAA), and PT Jaya Trishindo Tbk (HELI).